Posttreatment HRP2 Clearance in Patients with Uncomplicated Plasmodium falciparum Malaria. (6th December 2017) - Plucinski, Mateusz M; Dimbu, Pedro Rafael; Fortes, Filomeno; Abdulla, Salim; Ahmed, Saumu; Gutman, Julie; Kachur, S Patrick; Badiane, Aida; Ndiaye, Daouda; Talundzic, Eldin; Lucchi, Naomi; Aidoo, Michael; et al.
Abstract : Plasmodium falciparum histidine-rich protein 2 antigen is cleared in accordance with first-order kinetics after successful antimalarial treatment. Deviations from this pattern of clearance are predictive of future treatment failure, even in the absence of other indications of inadequate response to treatment. Abstract: Background: The response to antimalarial treatment is assessed using serial microscopy. New techniques for accurate measurement of the Plasmodium falciparum histidine-rich protein 2 (HRP2) antigen have allowed for monitoring of the antigen concentration over time, offering a potential alternative for assessing treatment response. Methods: Posttreatment HRP2 concentrations were measured in samples obtained longitudinally from 537 individuals with P. falciparum malaria who were participating in efficacy trials in Angola, Tanzania, and Senegal. The HRP2 half-life was estimated using a first-order kinetics clearance model. The association between the HRP2 concentration 3 days after treatment and recrudescence of infection was assessed. Results: Despite substantial variation in HRP2 concentrations among participants at baseline, concentrations consistently showed a first-order exponential decline. The median half-life of HRP2 was estimated to be 4.5 days (interquartile range [IQR], 3.3–6.6 days) in Angola, 4.7 days (IQR, 4.0–5.9 days) in Tanzania, and 3.0 days (IQR, 2.1–4.5 days) in Senegal. The day 3 HRP2 concentration was predictive of eventual recrudescence, with an area under the receiver operating characteristic curve of 0.86 (95% confidence interval, .73–.99). Conclusions: Consistent HRP2 clearance dynamics following successful antimalarial treatment imply a common underlying mechanism of biological clearance. Patients who ultimately did not respond to treatment did not exhibit this same pattern of clearance, even in the absence of other indications of inadequate response to treatment.